Airbrushing of carbon nanotubes on glass fibers for electromagnetic shielding epoxy composites - Schuster W.R.* (2023)
© 2023 Associacao Brasileira de Polimeros. All rights reserved.Tricomponent epoxy-matrix nanocomposites were prepared by airbrushing multiwalled carbon nanotubes (MWCNT) on glass fiber fabric (GF), aiming to establish a scalable route to produce electromagnetic interference (EMI) materials. The MWCNT deposition on GF by airbrushing was evaluated by scanning electron microscopy (SEM), showing a very reasonable dispersion even at high MWCNT concentrations. Electrical conductivity measurements have shown a maximum of 1.2x10-3 S/cm for GF with 3.4 wt% MWCNT. Electromagnetic shielding response for GF airbrushed with MWCNT and epoxy-matrix nanocomposites were analyzed considering reflection, absorption and transmission mechanisms and have shown an increasing trend as the MWCNT content increases, reaching the best result of 7.6 dB of shielding effectiveness (SE) in X-band spectra for the composite with 3.4 wt% MWCNT. The results showed that the airbrushing process can be a promising and easy route for manufacturing of MWCNT/GF/epoxy nanocomposites.